Synchronous Recovery of Waveforms From Dynamic Phasors Models of LCC-HVDC Links - Leonardo Pinto de Almeida; Sergio Gomes; Thiago J. Masseran A. Parreiras (IEEE Access)
LCC-HVDC links are used worldwide for long-distance bulk power transmission in large scale power systems. In this technology, commutation failure phenomena may occur, where transient power interruptions of HVDC links may lead the system to electromechanical instability. For power system simulations with HVDC transmission, the dynamic phasor methodology has advantages for considering simultaneously the electromechanical and electromagnetic transients, in particular, the simulation of commutation failures and their impacts in transient stability. However, when using dynamic phasors, the full harmonic contents of the HVDC variables are missing, which may worsen the accuracy of commutation failure simulations. This paper proposes a methodology, named Synchronous Recovery of Waveforms from Dynamic Phasor Model (SRWDPM) for obtaining accurate waveforms of the HVDC variables from dynamic phasor models. The main benefits of SRWDPM are these accurate waveforms and their use for adequate commutation failure simulations using efficient fundamental frequency dynamic phasor models. These accurate waveforms were previously only available in EMT programs or in expensive dynamic phasor models of high-order harmonics. The methodology is based on numerical integration of a small subsystem of each HVDC converter using instantaneous values obtained from dynamic phasors as input variables. SRWDPM is solved synchronously with the dynamic phasor solution and the waveforms are comparable to those obtained in electromagnetic transient programs with discontinuities and without harmonic truncation. The proposed methodology is general, it can be applied to different dynamic phasor models for improving efficiency or accuracy. A benchmark system is used for illustrating the methodology application.